2017
DOI: 10.1016/j.apenergy.2017.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the operation characteristics of an air-driven free-piston linear expander

Abstract: Free-piston engine is a kind of linear internal combustion engine, and shows advantages on simple mechanical structure, low frictional losses, high thermal efficiency and operational flexibility. In this research, an experimental test rig of a dual-piston air-driven free-piston linear expander (FPLE) is established using the FPE concept. A linear generator is used to convert the mechanical work of the pistons into electricity during the expansion process. The piston dynamics, the output voltage of the generato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…When considering ORC systems of net electrical power output around 1 kWe, scroll and screw expanders are a well-known technology for energy conversion, but when the temperature of the hot source falls below 100 • C, other machines have to be used. For example, an innovative way to generate a small amount of electrical power (a few Watts) is to utilize free-piston expanders [5,6]. From the experimental side, the use of a positive displacement machine requires a specific test-rig to reproduce the actual operating conditions in terms of pressure, fluid characteristics and loads.…”
Section: Introductionmentioning
confidence: 99%
“…When considering ORC systems of net electrical power output around 1 kWe, scroll and screw expanders are a well-known technology for energy conversion, but when the temperature of the hot source falls below 100 • C, other machines have to be used. For example, an innovative way to generate a small amount of electrical power (a few Watts) is to utilize free-piston expanders [5,6]. From the experimental side, the use of a positive displacement machine requires a specific test-rig to reproduce the actual operating conditions in terms of pressure, fluid characteristics and loads.…”
Section: Introductionmentioning
confidence: 99%
“…The Linear Engine Generator is linear 'crank-less' power device that couples a linear internal combustion engine with a linear electric generator, it uses conventional diesel or Otto cycles [4,14,15]. The piston of the engine is connected with the translator of the generator.…”
Section: Linear Engine Generator Technologymentioning
confidence: 99%
“…Wang et al tested an air-driven Free Piston Linear Expander (FPLE). The results showed that the operation frequency is more sensitive with the driven pressure [12].…”
Section: Introductionmentioning
confidence: 98%